Mineralocorticoid Receptor Activation Contributes to the Supine Hypertension of Autonomic Failure. Issue 2 (February 2016) - Arnold, Amy C.; Okamoto, Luis E.; Gamboa, Alfredo; Black, Bonnie K.; Raj, Satish R.; Elijovich, Fernando; Robertson, David; Shibao, Cyndya A.; Biaggioni, Italo
Abstract : Primary autonomic failure is characterized by disabling orthostatic hypotension, but at least half of these patients have paradoxical supine hypertension. Renin–angiotensin mechanisms were not initially thought to contribute to this hypertension because plasma renin activity is often undetectable in autonomic failure. Plasma aldosterone levels are normal, however, and we recently showed that plasma angiotensin II is elevated and acts at AT1 (angiotensin type 1) receptors to contribute to hypertension in these patients. Because aldosterone and angiotensin II can also bind mineralocorticoid receptors to elevate blood pressure, we hypothesized that mineralocorticoid receptor activation plays a role in the hypertension of autonomic failure. To test this hypothesis, we determined the acute effects of the mineralocorticoid receptor antagonist eplerenone (50 mg, oral) versus placebo on supine blood pressure in a randomized, double-blind, crossover study. Medications were given at 8:00 PM with blood pressure recorded every 2 hours for 12 hours. Ten primary autonomic failure patients with supine hypertension completed this study (7 pure autonomic failure, 2 multiple system atrophy, 1 parkinson's disease; 7 male; 70±2 years of age). Eplerenone maximally reduced supine systolic blood pressure by 32±6 mm Hg at 8 hours after administration (versus 8±10 mm Hg placebo, P =0.016), with no effect on nocturia (12-hour urine volume: 985±134 mL placebo versus 931±94 mL eplerenone, P =0.492; nocturnal weight loss: −1.19±0.15 kg placebo versus −1.18±0.15 kg eplerenone, P =0.766). These findings suggest that inappropriate mineralocorticoid receptor activation contributes to the hypertension of autonomic failure, likely independent of canonical mineralocorticoid effects, and provides rationale for use of eplerenone in these patients.